2002
DOI: 10.1046/j.1439-0485.2002.02763.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet of Phycis blennoides (Gadidae) in Relation to Fish Size and Season in the Western Mediterranean (Spain)

Abstract: Abstract. Despite its commercial value, little is known about the feeding ecology of the greater forkbeard, Phycis blennoides (Brünnich 1768). The stomach contents of 2631 greater forkbeard were taken at monthly intervals off the coast of the Gulf of Valencia (western Mediterranean). They were examined in order to assess the diet and to determine the fish size‐ and season‐related dietary variation of the species. Prey items were identified to the lowest taxonomic level possible. The basic food consisted of ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
3
19
0
Order By: Relevance
“…Its presence in this 'benthic' group confirms observations by Ross & Quattrini (2007) (29) mysids and teleosts ( blennoides in the first group seems to be due to its feeding on epibenthic species, mostly decapods, mysids and teleosts (Morte et al 2002). However, P. blennoides was observed displaying station-holding behaviour slightly above the bottom in the Bay of Biscay (Uiblein et al 2003).…”
Section: Fauna Composition and Behavioursupporting
confidence: 85%
“…Its presence in this 'benthic' group confirms observations by Ross & Quattrini (2007) (29) mysids and teleosts ( blennoides in the first group seems to be due to its feeding on epibenthic species, mostly decapods, mysids and teleosts (Morte et al 2002). However, P. blennoides was observed displaying station-holding behaviour slightly above the bottom in the Bay of Biscay (Uiblein et al 2003).…”
Section: Fauna Composition and Behavioursupporting
confidence: 85%
“…As diet is the main source of contamination for fishes (Hall et al, 1997), understanding what food source fuels deep-sea organisms is crucial to better understand their contamination patterns. Some early papers performed extensive studies of the diet of some teleosts and shark species (eg Carrassón et al, 1992;Macpherson, 1979;1981;Morte et al, 2002) whereas more recent research characterized the OM reaching deep zones (Canals et al, 2006;Heussner et al, 2006;Pasqual et al, 2013;Sanchez-Vidal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Three fish (blackbelly rosefish Helicolenus dactylopterus, four-spot megrim Lepidorhombus boscii, and greater forkbeard Phycis blennoides) and two shark species (black-mouthed dogfish Galeus melastomus and lesser spotted dogfish Scyliorhinus canicula) were targeted on the basis of their similar high trophic position, their abundance and their importance in slope and canyons community functioning (Carrassón and Cartes, 2002;Morte et al, 2002;Fanelli et al, 2013;Goujard et al, 2013;Papiol et al, 2013;Tecchio et al, 2013;Fabri et al, 2014;Cresson et al, 2014).In addition, there is a great concern for the chemical contamination in deep-living fish species, the biological and ecological specificities of which, e.g. longer lifespan or reduced growth rate, made them at risk for chemical contamination, as confirmed by high values recorded in those species previously al., 2014).…”
Section: Species Selection and Samplingmentioning
confidence: 99%
“…Earlier analyses of stomach contents revealed that carnivory is the prevalent feeding behavior in this deep ecosystem, even if a wide range of prey can be consumed, from benthic invertebrates to fish (e.g. Macpherson, 1981;Carrassón and Cartes, 2002;Morte et al, 2002). The recent generalized use of C and N stable isotopes allow an integrated view of the food web organization, tracking organic matter fluxes all along the whole trophic webs (e. g. Polunin et al, 2001;Fanelli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%